HUBUNGAN ANTARA RATA-RATA UAN DENGAN IPK TIGA SEMESTER AWAL MAHASISWA JURUSAN BIOLOGI FMIPA UNM ANGKATAN TAHUN AKADEMIK 2008/2009 - Hamka, Lodang; Muhiddin, Palennari (Fakultas MIPA UNM, 2010)
This research is correlation research to see the relationship between the average of students in national examination with GPA at three former semesters of the students of Biology Department, Science Faculty, State University of Makassar. The population was all students biology department in academic year 2008/2009 which consists of 147. The samples were taken purposively from 2008/2009 which consists of 82. The data were used secondary data average national examination student of biology department in academic year 2008/2009 and GPA at three former semester of the student of Biology Department in academic year 2008/2009. The data were analyzed quantitatively with percentages and inferential analysis using product moment correlation test. The research result concluded that there was no relation between the averages of students? achievement in national examination with the GPA at three former semesters of the student of biology department State University of Makassarin academic year 2008/2009. Bionature Vol. 11 (2): Hlm: 85 - 88, Oktober 2010ISSN: 1411-4720Hubungan antara Rata-Rata UAN dengan IPKTiga Semester Awal Mahasiswa Jurusan Biologi FMIPA UNMAngkatan Tahun Akademik 2008/2009